Research Advances in Clinical Strategies and Preclinical Models for Syphilis Relapse - Chen X (Infection and Drug Resistance)
Xia Chen Department of Dermatology, Chengdu Second People’s Hospital, Chengdu, People’s Republic of ChinaCorrespondence: Xia Chen, Department of Dermatology, Chengdu Second People’s Hospital, No. 10 Qingyun South Street, Jinjiang District, Chengdu, 610021, People’s Republic of China, Tel +86-18702880223, Email chenxiacd@163.comAbstract: Syphilis relapse remains a significant clinical challenge, with reported recurrence rates that can be substantial, particularly in immunocompromised individuals. This review synthesizes current advancements in clinical strategies and preclinical models for managing syphilis recurrence. Clinically, penicillin-based regimens, including benzathine penicillin G and procaine penicillin, are the cornerstone of treatment, while alternatives such as ceftriaxone or doxycycline are reserved for penicillin-allergic patients. Some research explores the potential of adjunctive therapies to enhance pathogen clearance and reduce relapse risk, though these are not yet standard practice and require substantial further evidence. Rigorous serological monitoring via quantitative nontreponemal tests (eg, RPR/VDRL) and clinical evaluation is essential for therapeutic adjustment. Preclinically, in vitro cultivation systems and animal models, particularly rabbit and humanized mouse models, have provided critical insights into Treponema pallidum persistence mechanisms, immune evasion strategies, and therapeutic testing. These models facilitate pathogenesis studies, drug discovery, and vaccine development, offering translational value for clinical applications. Despite progress, challenges such as interspecies physiological differences which impact the direct applicability of findings to human relapse scenarios, T. pallidum’s fastidious growth requirements, and ethical constraints persist. Future research should prioritize elucidating relapse mechanisms, optimizing therapeutic protocols, and developing advanced diagnostics to mitigate syphilis recurrence and its public health burden. This comprehensive overview underscores the integration of clinical and preclinical findings to inform evidence-based management of syphilis relapse, highlighting the critical need for models that more accurately recapitulate human disease persistence to overcome existing translational gaps.Keywords: syphilis recurrence, antimicrobial therapy, immunotherapy, animal models, Treponema pallidum